ISOLATION CHARACTERISTICS AND ANTIMICROBIAL RESISTANCE OF COMMON BACTERIAL PATHOGENS IN ICU AND NON-ICU DEPARTMENTS AT TRA VINH GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the bacterial isolation characteristics from clinical specimens and to compare the antimicrobial resistance rates of selected common pathogens between the intensive care unit (ICU) and non-ICU departments at Tra Vinh General Hospital in 2025.Materials and methods: A retrospective cross-sectional descriptive study was conducted on 9,543 clinical specimens and antimicrobial susceptibility testing results of the first bacterial isolates that met the selection criteria at Tra Vinh General Hospital in 2025. Culture results were analyzed, with a focus on several commonly isolated bacterial species.Results: Among 9,543 clinical specimens, 3,539 yielded positive bacterial cultures. Antimicrobial resistance analysis was performed at the isolate level using eligible first bacterial isolates with available susceptibility testing results. Escherichia coli and Staphylococcus aureus were the most common Gram-negative and Gram-positive bacteria, respectively. Compared with isolates from non-ICU departments, isolates from the ICU showed higher resistance rates to many clinically important antibiotics. This was particularly evident for Acinetobacter baumannii complex, with resistance rates in the ICU ranging from 94.0% to 100% for most of the antibiotics investigated.Conclusion: Gram-negative bacteria predominated among clinical specimens collected at Tra Vinh General Hospital in 2025. Isolates from the ICU showed higher levels of antimicrobial resistance than those from non-ICU departments, especially Pseudomonas aeruginosa and Acinetobacter baumannii complex.
Keywords: bacterial isolates; antimicrobial resistance; ICU; antimicrobial susceptibility testing; Gram-negative bacteria.